A Study of Sensitivity Improved Probe Using Hyperbolic Metamaterial for Optical Fiber SPR (OFSPR)-based Refractive Index Sensor - Dubey S.K.; Kumar A.; Pandey A.; Pathak A.; Srivastava S.K. (My University, 2025)
In this work, we theoretically study the plasmonic behavior of Ag and Au with a hyperbolic metamaterial (HMM) and propose a numerical simulation of a D-shaped surface plasmon resonance (SPR)-based refractive index sensor in the near-infrared (NIR) region using the finite element method (FEM). The design of the sensing probe consists of a grating structure of metal (Ag/Au) coated with an alpha-phase molybdenum trioxide (α-MoO3) HMM layer. The sensing layer of α-MoO3 over Ag/Au is responsible for the enhanced sensitivity of the optical fiber SPR sensor. This is attributed to the better SPR generation with a metal-dielectric layer. Numerical results show that the proposed sensor is able to detect a refractive index over a large dynamic range of 1.33 to 1.4. With the help of the optimized structure, we achieve maximum sensitivity of 8.31 μm /RIU and 9.89 μm /RIU for the Ag-α-MoO3- and Au-α-MoO3-based grating structure, respectively. These results show excellent response in comparison with other reported works. © 2022, The Author(s), under exclusive licence to Springer Science+Business Media, LLC, part of Springer Nature.